Laboratory Detection of Toenail Onychomycosis Using Malt Extract Agar in Students - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo (Biology, Medicine, & Natural Product Chemistry, 2025)
Onychomycosis is a common nail disorder caused by dermatophytes, non-dermatophyte molds, and yeasts. Despite being more prevalent in older adults, it is increasingly reported among younger populations, including university students, due to lifestyle factors and communal exposures. Rapid and accurate diagnosis is critical for effective management, but conventional methods remain limited in sensitivity. This study aimed to evaluate the prevalence and etiological profile of toenail onychomycosis among university students using potassium hydroxide (KOH) microscopy and Malt Extract Agar (MEA) culture. A total of 98 students with clinical signs of onychomycosis provided toenail specimens. Direct microscopy examination with 20% KOH was performed, followed by culture on MEA at 28–30 °C for up to 21 days. Fungal isolates were identified based on macroscopic and microscopic morphology. Statistical analysis assessed associations between clinical features and culture results. KOH microscopy detected fungal elements in 59.2% of specimens, while MEA culture yielded growth in 63.3%. When combined, the overall prevalence of confirmed onychomycosis was 71.4%. Trichophyton rubrum was the most frequent isolate (35.5% of positive cultures), followed by non-dermatophyte molds such as Aspergillus and Fusarium, and yeasts including Candida albicans and Candida parapsilosis. Nail thickening and discoloration were significantly associated with culture positivity (p < 0.05). Onychomycosis is prevalent among university students, with MEA culture providing superior diagnostic yield compared to KOH microscopy alone. The identification of non-dermatophyte molds and yeasts underscores the importance of comprehensive diagnostic strategies for guiding effective treatment. Future studies should combine culture and molecular methods to enhance detection accuracy and clarify the clinical significance of emerging pathogens.